Economic evaluation of knee arthroscopy treatment in a general hospital - Patricia Blatnik; Matej Tušak; Štefan Bojnec; Arjana Brezigar Masten (Medicinski glasnik, 2017)
Aim: The economic evaluation of medical programs applies procedures that search for and ensure the cheapest methods of medical treatment with the best feasible health results. The aim of this study was to thoroughly examine both the costs and results of medical outcomes, which were based upon two alternative methods of treatment. The purpose was to offer obtained information to the medical profession and hospital management, since they must decide on how to use the funds designed for knee arthroscopy surgery. Methods: A cost-utility analysis of two competitive treatments for knee arthroscopy was evaluated: the first one was executed by a standard department of surgery and the second one for the implementation within the framework of ambulatory treatment. Results: The direct costs of the existing knee arthroscopy surgery amount to 930.39 euro, while the alternative treatment amount to 419.80 euro. The second alternative treatment would significantly reduce labor costs, depreciation costs and material costs. The implementation of the second alternative would reduce the total cost by 54.88%. Conclusion: Outpatient surgical procedures can bring numerous potential advantages such as lower costs and unchanged or improved medical outcomes, when compared to the classical method of outpatient treatment. The results show that the outpatient treatment does not sacrifice quality in order to reduce hospital costs.
Keywords: costs and cost analysis; quality-adjusted life years; inpatients; outpatients; health care economics and organizations